Transcription factor TFIIH and DNA endonuclease Rad2 constitute yeast nucleotide excision repair factor 3: implications for nucleotide excision repair and Cockayne syndrome. - Habraken, Y (1996)
Nucleotide excision repair (NER) of ultraviolet light-damaged DNA in eukaryotes requires a large number of highly conserved protein factors. Recent studies in yeast have suggested that NER involves the action of distinct protein subassemblies at the damage site rather than the placement there of a "preformed repairosome" containing all the essential NER factors. Neither of the two endonucleases, Rad1-Rad10 and Rad2, required for dual incision, shows any affinity for ultraviolet-damaged DNA. Rad1-Rad10 forms a ternary complex with the DNA damage recognition protein Rad14, providing a means for targeting this nuclease to the damage site. It has remained unclear how the Rad2 nuclease is targeted to the DNA damage site and why mutations in the human RAD2 counterpart, XPG, result in Cockayne syndrome. Here we examine whether Rad2 is part of a higher order subassembly. Interestingly, we find copurification of Rad2 protein with TFIIH, such that TFIIH purified from a strain that overexpresses Rad2 contains a stoichiometric amount of Rad2. By several independent criteria, we establish that Rad2 is tightly associated with TFIIH, exhibiting an apparent dissociation constant < 3.3 x 10(-9) M. These results identify a novel subassembly consisting of TFIIH and Rad2, which we have designated as nucleotide excision repair factor 3. Association with TFIIH provides a means of targeting Rad2 to the damage site, where its endonuclease activity would mediate the 3' incision. Our findings are important for understanding the manner of assembly of the NER machinery and they have implications for Cockayne syndrome.